陈翠梅独立电影中的马来西亚华人离散情结 = Diasporic depiction of Malaysian Chinese in independent flims of Tan Chui Mui - 方凤凰 Fong, Patricia Feng Huang (2014)
本文将以马来西亚独立电影的核心人物陈翠梅为研究对象，探讨陈翠梅的影视作品如何再现马来西亚华人的离散情结。解析马来西亚华人因国家政策产生离散情结，并追溯华裔马来西亚独立电影人的兴起原因和目前马来西亚电影的状况。以此作为基础，分析陈翠梅的五部作品中的马来西亚华人离散意识。作品的分析包括《南国以南》中体现的原乡情结、《一个未来》对马来西亚进行的批判、《爱情征服一切》所表达的离散族群对于“回归”理想家园的向往、《丹绒马林有棵树》中积极寻找“家”的态度、和《每一天每一天》中对于现实的失望与无奈。本文希望借由陈翠梅的论述真实反映马来西亚华人的面貌与在地处境，并展现这个新领域的价值，为马来西亚独立电影研究做出贡献。This report focuses on filmmaker Tan Chui Mui, the core member of this Malaysia independent filmmaking movement, analyzing the diasporic depictions of Malaysian Chinese in her works. The report will start off with the exploration on how the local Chinese community develops diasporic consciousness in relation to the sociopolitical scene of Malaysia, and discussion of the Malaysia independent filmmaking industry to act as a foundation to support the later film analysis. Tan Chui Mui’s South of South, One Future, Love Conquers All, A Tree in Tanjung Malim, and Everyday Everyday will be analysed in details. This report aims to provide a true reflection of the Malaysian Chinese community, and contributes to the study of Malaysian independent filmmaking by showcasing the value of this industry.